2020
DOI: 10.1111/jcmm.14998
|View full text |Cite
|
Sign up to set email alerts
|

KRT8 phosphorylation regulates the epithelial‐mesenchymal transition in retinal pigment epithelial cells through autophagy modulation

Abstract: Proliferative vitreoretinopathy (PVR) is a severe ocular disease which results in complex retinal detachment and irreversible vision loss. The epithelial‐mesenchymal transition (EMT) of retinal pigment epithelial (RPE) cells is considered to be critical in the pathogenesis of PVR. In this study, we focused on the potential impact of keratin 8 (KRT8) phosphorylation and autophagy on TGF‐β2–induced EMT of RPE cells and explored the relationship between them. Using immunofluorescence and Western blot analysis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Our mechanistic investigation revealed that the STIM2-KRT8 axis is critical in CCA metastasis. KRT8 (keratin 8) is an epithelial marker and one of the most important keratin proteins (28). KRT8 and its filament partner, KRT18, have been found to control the cellular response to stress stimuli and contribute to cell resistance to apoptosis, in addition to maintaining cell mechanical integrity (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our mechanistic investigation revealed that the STIM2-KRT8 axis is critical in CCA metastasis. KRT8 (keratin 8) is an epithelial marker and one of the most important keratin proteins (28). KRT8 and its filament partner, KRT18, have been found to control the cellular response to stress stimuli and contribute to cell resistance to apoptosis, in addition to maintaining cell mechanical integrity (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although aberrant KRT8 expression has been studied in a variety of malignancies ( 9 , 12 15 , 17 , 18 ), the underlying mechanisms and role of KRT8 in LUAD still remain unclear. KRT8 plays a key role in lung disease, such as lung fibrosis ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) is a biologic phenomenon that can alter the state of cells along a phenotypic spectrum and cause transcriptional rewiring to produce distinct tumor cell subpopulations ( 25 ). It is reported that KRT8 can participate in cell migration and invasion through EMT ( 18 ). In LUAD, the results indicated that KRT8 knockdown downregulated EMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that these floating pigment cells, presumably RPE cells, attach to the surface of the retina, undergo EMT and migrate as fibrotic cells 29 . Miao et al 30 found that the loss of cell‐cell adhesion was the cause of EMT process and RPE cell proliferation. The epithelial markers, involving E‐cadherin and ZO‐1, have been proven to play an important role in maintaining cell proliferation and epithelial differentiation 31,32 .…”
Section: Discussionmentioning
confidence: 99%